Comparing competitive anxiety among male and junior football players at Al Wathba Sports Club (Journal of Hama University, 2026)
The study aimed to identify the level of sports competition anxiety among male and junior football players at Al Wathba Sports Club and compare them To achieve this, the study was conducted on a sample of (40) players, including (20) male players and (20) junior players. To collect the study data and achieve its objectives, the descriptive approach was used, and the Arabic image was used to test sports competition anxiety (Alawi, 1998). The results of the study showed that there were no differences between the levels of anxiety among men and juniors in this club.
Keywords: Anxiety, sports competition, male and female soccer players.